Satellite based potential fishing zone (PFZ) advisories - acceptance levels and benefits derived by the user community along the Kerala coast - Nair, Preetha G; Pillai, Narayana (Indian Journal of Fisheries, 2012)
Intensive validation studies of potential fishing zone (PFZ) advisories generated using integration of ocean colour monitor (OCM) derived chlorophyll concentration and advanced very high resolution radiometer (AVHRR) derived sea surface temperatures (SST) were undertaken by the Indian National Centre for Ocean Information Services (INCOIS) along Kerala coast during the period 2003-2011. There is a positive relationship between PFZ advisories and occurrence/abundance of commercially important pelagic fishes such as oilsardine, Indian mackerel, anchovies, carangids and coastal tunas. Fishing operations undertaken on or closer to dates on which related SST/chlorophyll images have been received yielded positive results. As the gap increases, the yield within PFZ is likely to come down unless the features remain more or less in the same location as revealed by succeeding satellite imagery. The present paper revealed that the fish catch (CPUE) and net profit earned are higher within PFZ compared to the results of operations outside PFZ. The usefulness of PFZ advisories, the only short term marine fishery forecast available in the country for fisherfolk towards obtaining comparatively higher catch per unit effort for the above mentioned major pelagics is proved beyond doubt from the results of more than 100 controlled experiments conducted within and outside PFZ with identical fishing gear along Kerala coast.